Environmentalism after the Pandemic - Elliot Honeybun-Arnolda; Tim O’Riordan (Journal for the History of Environment and Society, 2020)
The second half of the twentieth century witnessed the explosive emergence of environmentalism accompanied by increasingly influential scientific, regulative and managerial roles for the environmental sciences. Since then, there has been a comprehensive increase of awareness and understanding of a whole spectrum of global to local environmental and socio-cultural dilemmas. Environmentalism has experienced a complicated set of tendentious relations with the various forms of capitalism. We argue here that any transformation to truly sustainable futures requires either a transformative integration of green growth within a modified capitalism, or a progressive shift to radically new ways of experiencing and living around sustainable localism. The pandemic has brought the world extraordinarily almost to a halt. It has offered a unique opportunity to consider, debate, and possibly implement sustainable livelihoods in myriads of different cultural and political settings via progressive social, political and economic reforms. By reconceptualising historical ideas of environmentalism into a new set of global to local arrangements post-pandemic, we can begin to shape and to live into sustainability, ideally across the whole planet. It is vital to progress with hope and through the yearnings of young people, and not with despair and through degeneration by clinging onto the old ways.